THE INFLUENCE OF THE AGROFORESTRY SYSTEM ON THE INCOME OF THE TANJUNG BERINGIN VILLAGE COMMUNITY - Helida, Asvic; Hidayat, Yayat; Ardiyansyah, Didi; syachroni, sasua hustati (Sylva Jurnal Ilmu-ilmu Kehutanan, 2023)
Agroforestry is a land management system that combines agricultural production plants with forestry plants. Based on economic aspects, implementing an agroforestry system combines several types of plants on one land, this can increase crop productivity. so that the total income after harvest will be abundant. This research aims to identify the agroforestry planting patterns implemented and analyze farmers' income in Tanjung Beringin Village, Tanjung Lubuk District, Ogan Komering Ilir Regency. This research was carried out in Tanjung Beringin Village, Tanjung Lubuk District, Ogan Komering Ilir Regency. The research method used is a descriptive qualitative method. The sampling technique used the Slovin formula with a total of 31 respondents. Data collection was carried out by giving questionnaires to respondents. The results of the research show that the community in Tanjung Beringin Village applies the Randome Mixture agroforestry planting pattern by implementing agricultural crops and forestry plants planted irregularly according to the wishes of farmers. Respondents' household income comes from fruit sales, income from secondary crops. The contribution of agroforestry income is greater than income originating from non-agroforestry (Rp. 80,000,000,-). The results of agroforestry in Tanjung Beringin Village, Tanjung Lubuk District, Ogan Komering Ilir Regency contributed to an income (all respondents) of Rp. 98,906,000,- Per year.Key words: Agroforestry, agroforestry system, cropping patterns, income, contribution